A service level agreement framework of cloud computing based on the Cloud Bank model - Fengchuan Zhu; Hao Li; Lu, J. (2012 IEEE International Conference on Computer Science and Automation Engineering, 2012)
The Cloud Bank model, which is derived from Grid bank [1], is a kind of commerce model of cloud computing that provides pay-as-you-go computing resources. In this model, Cloud Bank is an agent platform of resource transaction. Cloud computing uses the concept of service level agreement (SLA) to control the use and receipt of computing resources from, and by, Cloud Bank. As computing resources are provided in the form of services, Quality of Service (QoS) mechanisms are introduced to solve any quality of service problems. This paper presents a framework of Service Level Agreements in the Cloud Bank model (CBSLA), QoS attributes is added to the CBSLA to guarantee the quality of service. All the transactions of cloud bank are based on the CBSLA agreement.